Financial inclusion and small enterprise growth in Africa: Emerging perspectives and research agenda - John E. Kuada (African Governance and Development Institute (AGDI), 2021)
Purpose - The purposes of this paper are to review the streams of studies that link financial inclusion to small enterprise growth in Sub-Sahara Africa (SSA), to identify the research gaps they provide, and to prepare an agenda for future research in the field. Design/methodology/approach - The study employs systematic literature search method to identify relevant literature from journals. It then adopts a narrative approach for the review, highlighting the findings from the prior studies and gaps requiring research attention. Findings - The discussions reveal that there is a need for future studies that can unpack small enterprise growth determinants, identify growth-enabling entrepreneurial characteristics and examine the contextual variabilities that shape their effectiveness. Originality/value - There is currently no comprehensive/integrated review exploring the link between financial inclusion and small enterprise growth in SSA. This review therefore provides insights that contribute to the development of this stream of research.
Keywords: 330; Financial inclusion; entrepreneurship; small businesses; enterprise growth; Africa